Imperfect Vertical Transmission of the Endophyte Neotyphodium in Exotic Grasses in Grasslands of the Flooding Pampa - Gundel, Pedro E. (2008)
Fil: Gundel, Pedro E. Universidad de Buenos Aires. Facultad de Agronomía. Instituto de Investigaciones Fisiológicas y Ecológicas vinculadas a la Agricultura; Argentina.